Fulfilling an Unmet Need: Roles for Clinical Pharmacists in Preconception Care. Issue 2 (5th February 2016) - DiPietro Mager, Natalie A.
Abstract : Preconception care refers to a set of interventions that identify and address biomedical, behavioral, and social risks to a woman's health that may negatively impact a future pregnancy. A great need for preconception care currently exists in the United States, and women's attitudes about discussions with health care providers about healthy and safe pregnancies are positive. Clinical pharmacists are well positioned to work with other health care and public health professionals to ensure that all women of childbearing potential have access to preconception care. As part of the collaborative health care team, clinical pharmacists can directly provide services or support and referrals to other members of the health care team or to community resources through clinical‐community linkages. Specifically, clinical pharmacists can provide education, counseling, and/or services to women to address family planning, medication and disease state management, immunizations, screenings, health promotion, and substance use. Clinical pharmacists can also impact preconception care through drug information services, advocacy, and research. Preconception care services can be incorporated into daily pharmacy practice, and there are potential means for reimbursement. Multiple roles exist for clinical pharmacists to fulfill unmet needs in preconception care.